Agendamelding and COVID-19: the dance of horizontal and vertical media in a pandemic - Minooie, Milad; Taylor, J. Benjamin; Vargo, Chris J. (Frontiers in Political Science, 2023)
How are attitudes formed in the 21st Century, and who sets the agenda for initial COVID-19 coverage in the United States? We explore these questions using a random sample of 6 million tweets from a population of 224 million tweets collected between January 2020 and June 2020. In conjunction with a content analysis of legacy media such as newspapers, we examine the second-level agendamelding process during the onset of the COVID-19 pandemic in the United States. The findings demonstrate that in the early weeks of the pandemic, public opinion on Twitter about the virus was distinctly different than the coverage of the issue in the traditional media. The attributes used to describe it on social media demonstrate users relying on their past experiences and personal beliefs to talk about the virus. In the 1st week of February, public opinion, traditional media, and social media converged, but traditional media soon becomes the main agenda setter of COVID-19 for 13 weeks. However, for the final 5 weeks of our sample, traditional media are taken over by social media. The findings also show that, except for a few weeks at the onset of the outbreak, Twitter users relied on their personal experiences far less than what statistical models predicted and allowed. Instead, traditional media and social media to shape their opinion of the issue.